Increasing Endoglin Deletion in Endothelial Cells Exacerbates the Severity of Brain Arteriovenous Malformation in Mouse - Zahra Shabani; Leandro Barbosa Do Prado; Rui Zhang; Wan Zhu; Sonali S. Shaligram; Alka Yadav; Calvin Wang; Hua Su (Biomedicines, 2024)
Endoglin (ENG) mutation causes type 1 hereditary hemorrhagic telangiectasia (HHT1). HHT1 patients have arteriovenous malformations (AVMs) in multiple organs, including the brain. In mice, Eng deletion induced by R26RCreER or SM22αCre leads to AVM development in the brain and other organs. We hypothesized that an increase in Eng- negative ECs will enhance AVM severity. To increase EC Eng deletion, we used a codon-improved cre (icre), which is more potent in recombination of the floxed alleles than the wild-type (WT) cre. R26RCreER;Engf/f mice that have a Rosa promoter driving and tamoxifen (TM)-inducible WT cre expression globally, and PdgfbiCreER;Engf/f mice that have a Pdgfb promoter driving and TM-inducible icre expression in ECs were treated with three intra-peritoneal injections of TM (2.5 mg/25 g of body weight) to delete Eng globally or in the ECs. AAV-VEGF was stereotactically injected into the brain to induce brain focal angiogenesis and brain AVM. We found that icre caused more Eng deletion in the brain, indicated by a lower level of Eng proteins (p < 0.001) and fewer Eng-positive ECs (p = 0.01) than mice with WT cre. Mice with icre-mediated Eng deletion have more abnormal vessels (p = 0.02), CD68+ macrophages (p = 0.002), and hemorrhage (p = 0.04) and less vascular pericyte and smooth muscle coverage than mice with WT cre. In addition, arteriovenous shunts were detected in the intestines of icre mice, a phenotype that has not been detected in WT cre mice before. RNA-seq analysis showed that 8 out of the 10 top upregulated pathways identified by gene ontology (GO) analysis are related to inflammation. Therefore, the increase in Eng deletion in ECs exacerbates AVM severity, which is associated with enhanced inflammation. Strategies that can reduce Eng-negative ECs could be used to develop new therapies to reduce AVM severity for HHT1 patients.